Pelatihan Jarimatika Pada Siswa Sekolah Dasar Negeri 4 Citeureup - M. Asep Syihabul Millah; Rihatul Jannah; Linda Linda; Minhatul Ma'arif; Ira Asyura; Asep Saefullah Kamali (Pusat Riset dan Inovasi Nasional, 2023)
Following the journey of mathematics at the elementary school level, students often hear complaints when they have to explore concepts such as addition, subtraction, multiplication, and division. In such a dilemma, the need for innovation becomes even more pressing, as a way to carve out a vibrant next generation. The author sees that in learning mathematics, grade 3 students at SD Negeri 4 Citeureup lack enthusiasm for mathematics because this subject is often considered difficult. Overall, the process of implementing community service with a focus on education uses the jarimatics method to increase enthusiasm or motivation in studying mathematics for Citeureup 4 public elementary school students. The results of community service activities include the following: (a) achievement of the target number of participants. (b) the accuracy and skill of students working on multiplication problems. (c) achievement of activity objectives. After a series of training activities were carried out, finally we provided feedback questions from students. Do they feel happy and more motivated in learning mathematics? They all agree that they are happy and feel more motivated. To increase students' interest and motivation in learning mathematics, teachers should use good and effective methods to move and motivate students to be active in learning mathematics.